Lagenorhynchus australis - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Lagenorhynchus australis (Peale, 1848). Mammalia and Ornithology, in U.S. Expl. Exped., 8: 33. TYPE LOCALITY: South Atlantic Ocean, off the coast of Patagonia, Argentina, "one day's sail north of the Straits of Le Maire between Staten Island and Cape San Diego." DISTRIBUTION: Cold temperate waters of Chile, Argentina, and Falkland Isis. COMMENT: Included in cruciger by Hershkovitz, 1966:67, but considered a distinct species by Rice, 1977, Brownell, 1974, in Brown, et al., eds., Antarctic Mammals, Folio 18, Amer. Geogr. Soc., 19 pp., 11 pls., and IWC, 1975, J. Fish Res. Bd. Can., 32: 875-983. PROTECTED STATUS: CITES - Appendix II as Order Cetacea. ISIS NUMBER: 5301411002012003001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Cetacea, pp. 290-304 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 293, DOI: 10.5281/zenodo.7352983